Expanding rural access to chronic pain care through nurse care management: A hybrid type I effectiveness-implementation trial protocol - Brennan Keiser; Karina Cortez; Elise Hoffman; Jin Wang; Kelly Reeves; Andrew Humbert; Robert W. Bailey; Stacy Shaw Welch; Sophia Jawort; Laura-Mae Baldwin; Caleb Holtzer; Hazel Tapp; et al. (PLoS ONE, 2026)
Background Chronic pain affects more than 20% of U.S. adults, with prevalence approaching 30% in rural communities. It can substantially impair physical functioning, mental health, and quality of life, and rural residents experience poorer pain-related outcomes. Effective care requires a comprehensive, multidisciplinary approach; however, rural primary care clinicians often rely on medications—particularly prescription opioids—as the predominant treatment despite limited evidence and substantial risks. Innovative strategies are needed to expand access to evidence-based, non-pharmacologic pain management in rural settings. Objective To determine the effectiveness of a nurse care management (NCM) model for chronic pain compared with usual care and to evaluate its implementation. Methods A pragmatic, hybrid type I effectiveness–implementation randomized controlled trial will be conducted from April 2026 to July 2028. A total of 450 adults with chronic pain and a Pain, Enjoyment of Life, and General Activity (PEG) scale total score ≥12 will be recruited from rural health systems. Rural eligibility will be verified using the Health Resources and Services Administration (HRSA) Rural Health Grants Eligibility Analyzer. Participants will be randomly assigned to the NCM intervention or to usual care using permuted block randomization with variable block sizes (4 or 6). The 6-month virtually delivered NCM intervention includes (1) cognitive behavioral therapy, (2) care coordination, and (3) referral to Tele-Enhance®Fitness , an instructor-led virtual group exercise program. The primary outcome is pain interference and intensity measured by the PEG scale. Secondary outcomes include pain catastrophizing, depression, anxiety, physical functioning, sleep disturbance, satisfaction with health, and opioid use. Implementation outcomes—reach, fidelity, feasibility, and sustainment—will be evaluated with the Practical, Robust Implementation and Sustainability Model (PRISM) framework. Discussion This pragmatic trial will assess the effectiveness of the NCM model for chronic pain care and collect implementation data to guide potential scale-up in rural primary care. Trial registration ClinicalTrials.gov identifier: NCT06407115.